Ch11Word - Page 1 Chapter 11 CHAPTER 11 – General...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Page 1 Chapter 11 CHAPTER 11 – General Rotation 1. ( a ) For the magnitudes of the vector products we have i × i = i i sin 0° = 0; j × j = j j sin 0° = 0; k × k = k k sin 0° = 0. ( b ) For the magnitudes of the vector products we have i × j = i j sin 90° = (1)(1)(1) = 1; i × k = i k sin 90° = (1)(1)(1) = 1; j × k = j k sin 90° = (1)(1)(1) = 1. From the right hand rule, if we rotate our fingers from i into j , our thumb points in the direction of k . Thus i × j = k . Similarly, when we rotate i into k , our thumb points along – j . Thus i × k = – j . When we rotate j into k , our thumb points along i . Thus j × k = i . 2. ( a ) We have A = – A i and B = B k . For the direction of A × B we have – i × k = – (– j ) = j , the positive y-axis . ( b ) For the direction of B × A we have k × (– i ) = – ( k × i ) = – ( j ) = – j , the negative y-axis . ( c ) For the magnitude of A × B we have A × B = A B sin 90° = AB . For the magnitude of B × A we have B × A = B A sin 90° = AB . This is expected, because B × A = – A × B . 3. The magnitude of the tangential acceleration is a tan = α r . From the diagram we see that α , r and a tan are all perpendicular, and rotating α into r gives a vector in the direction of a tan . Thus we have a tan = α × r . The magnitude of the radial acceleration is a R = ϖ 2 r = ϖ r ϖ = ϖ v . From the diagram we see that ϖ , v and a R are all perpendicular, and rotating ϖ into v gives a vector in the direction of a R . Thus we have a R = ϖ × v . 4. When we use the component forms for the vectors, we have A × ( B + C ) = [ A y ( B z + C z ) – A z ( B y + C y )] i + [ A z ( B x + C x ) – A x ( B z + C z )] j + [ A x ( B y + C y ) – A y ( B x + C x )] k = ( A y B z – A z B y ) i + ( A z B x – A x B z ) j + ( A x B y – A y B x ) k + ( A y C z – A z C y ) i + ( A z C x – A x C z ) j + ( A x C y – A y C x ) k = A × B + A × C ....
View Full Document

This note was uploaded on 03/16/2008 for the course PHYS phys230 taught by Professor Hadley during the Spring '08 term at A.T. Still University.

Page1 / 18

Ch11Word - Page 1 Chapter 11 CHAPTER 11 – General...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online